Assessment of thermally aged XLPE insulation material under extreme operating temperatures. (August 2020) - Lv, Hongkun; Lu, Tianhao; Xiong, Lingqi; Zheng, Xianggao; Huang, Yuyan; Ying, Mingliang; Cai, Jiecong; Li, Zhuo
Abstract: The degradation of cross-linked polyethylene (XLPE) insulation material is critical for the safe operation of cables. While there are extensive studies on the thermo-oxidative ageing of XLPE at or below 130 °C, the maximum overload conductor operating temperature, the short circuit temperature can rise above 150 °C, and the ageing patterns at these situations have not been fully understood. Here, chemical, crystalline structure, cross-linking density as well as the mechanical properties were characterized. The results demonstrate the importance of antioxidants in the high temperature situation. Before antioxidants are completely consumed, most of the mechanical and physicochemical properties remain stable. While antioxidant is depleted, the thermo-oxidative degradation is detrimental to the structure and properties of the insulation. The activation energy is around 160 kJ/mol for the thermo-oxidative ageing, from which the lifetime allowed before serious destruction of the insulation at different shortage or overload temperatures can be calculated. Highlights: Multiple characterizations are used to eluciate the ageing at high temperatures. Antioxidants are critical to resist thermal ageing of cross-linked polyethylene. The activation energy of thermal ageing is 160 kJ/mol. The lifetime of cable insulation in shortage situation can be predicted.